Recent advances in factor XII structure and function. Issue 5 (18th September 2022) - Shamanaev, Aleksandr; Litvak, Maxim; Gailani, David
Abstract : Purpose of review: Factor XII (FXII), the precursor of the protease FXIIa, contributes to pathologic processes including angioedema and thrombosis. Here, we review recent work on structure-function relationships for FXII based on studies using recombinant FXII variants. Recent findings: FXII is a homolog of pro-hepatocyte growth factor activator (Pro-HGFA). We prepared FXII in which domains are replaced by corresponding parts of Pro-HGA, and tested them in FXII activation and activity assays. In solution, FXII and prekallikrein undergo reciprocal activation to FXIIa and kallikrein. The rate of this process is restricted by the FXII fibronectin type-2 and kringle domains. Pro-HGA replacements for these domains accelerate FXII and prekallikrein activation. When FXII and prekallikrein bind to negatively charged surfaces, reciprocal activation is enhanced. The FXII EGF1 domain is required for surface binding. Summary: We propose a model in which FXII is normally maintained in a closed conformation resistant to activation by intramolecular interactions involving the fibronectin type-2 and kringle domains. These interactions are disrupted when FXII binds to a surface through EGF1, enhancing FXII activation and prekallikrein activation by FXIIa. These observations have important implications for understanding the contributions of FXII to disease, and for developing therapies to treat thrombo-inflammatory disorders.